Bacillus sp. and arbuscular mycorrhizal fungi consortia enhance wheat nutrient and yield in the second‐year field trial: Superior performance in comparison with chemical fertilizers - Yadav, Radheshyam; Ror, Pankaj; Beniwal, Rahul; Kumar, Sanjeev; Ramakrishna, Wusirika (Journal of applied microbiology, 2022)
Aims The aim of the study is to analyse the effect of microbial consortia for wheat biofortification, growth, yield and soil fertility as part of a 2‐year field study and compare it with the use of chemical fertilizers. Methods and Results A field trial (second year) was conducted with various combinations of plant growth–promoting bacteria (PGPB) and arbuscular mycorrhizal fungi (AMF) treatments, ranging from a single inoculant to multiple combinations. The microbial consortia used were Bacillus sp. and AMF based on first‐year field trial results. The consortia based on native (CP4) and non‐native (AHP3) PGPB (Bacillus sp.) and AMF performed better in terms of nutrients content in wheat grain tissue and yield‐related traits compared with chemical fertilizer treated and untreated control. Dual treatment of PGPB (CP4+AHP3) combined with AMF resulted in a significant increase in antioxidants. The spatial colonization of AMF in roots indicated that both the isolates CP4 and AHP3 were able to enhance the AMF colonization in root tissue. Furthermore, soil enzymes’ activities were higher with the PGPB and AMF combination giving the best results. A positive correlation was recorded between plant growth, grain yield and soil physicochemical parameters. Conclusions Our findings confirm that the combined treatment of CP4 and AHP3 and AMF functions as an effective microbial consortium with excellent application prospects for wheat biofortification, grain yield and soil fertility compared with chemical fertilizers. Significance and Impact of Study The extensive application of chemical fertilizers on low‐yielding field sites is a severe concern for cereal crops, especially wheat in the Asian continent. This study serves as a primer for implementing site‐specific sustainable agricultural‐management practices using a green technology leading to significant gains in agriculture.